Analisis Tindak Tutur Lokusi dan Perlokusi pada Tayangan Media Youtube Official INews Debat Perdana dan Ketiga Calon Presiden (Capres) Pemilu 2024 serta Pemanfaatannya sebagai Bahan Ajar di SMA - Yasih, Yasih (Jurnal Artikula, 2025)
This study aims to analyze locutionary and perlocutionary speech acts in the official iNews Youtube media broadcast regarding the first and third debates of the 2024 presidential candidates, and to explore its use as teaching materials at the high school level. Locutionary speech acts refer to what is literally said by the speaker, while perlocutionary speech acts relate to the effects or impacts caused by the utterance on the listener. Through a descriptive qualitative method on the debate video transcript, this study identified patterns of language use related to political communication strategies, arguments, and rhetoric applied by the presidential candidates. The overall data results that the author has obtained are 96 data. Based on the type of locutionary speech act 47 data consisting of 26 news sentences, 3 command sentences and 18 interrogative sentences. Then the type of perlocution 49 data consisting of happy 30 data, emotional 10 data, sad 6 data and afraid 3 data. This study also examines how the debate material can be used to teach language skills and critical thinking in high school, by providing concrete examples of how language can influence public opinion and political thought processes. The results of this study are expected to provide insight for educators on the application of speech act theory in practical contexts and add to the methods of learning language and political communication in high school